GNSS Applications and Methods. - Gleason, Scott (Artech House, 2009)
Placing emphasis on applications development, this unique resource offers a highly practical overview of GNSS (global navigation satellite systems), including GPS. The applications presented in the book range from the traditional location applications to combining GNSS with other sensors and systems and into more exotic areas, such as remote sensing and space weather monitoring. Written by leading experts in the field, this book presents the fundamental underpinnings of GNSS and provides you with detailed examples of various GNSS applications. Moreover, the software included with the book cont.